Major Factors Having Influence on the Subjective Happiness of Korean Youth; From the 13th KAHBOS Data (Medico Legal Update, 2020)
Background/Objectives: As a study of secondary analysis that analyzed the 13th (2017) Korean Adolescents’ Health Behavior Online Survey data second time, this is a descriptive study performed for the purpose of identifying the major factors having influence on the subjective happiness perceived by the youth.Methods/Statistical analysis: The subjects of the 13th (2017) survey were 64,991 students from total 800 schools and out of them, 62,276 students from 799 schools participated showing 95.8% of participation rate. For the general, physical and psychological factors, the complex sample frequency analysis and for the major factors having influence on the subjective happiness, the complex sample regression analysis were used.Findings: The age, grade, economic level, frequency of having breakfast per week, experience of receiving treatment by the violence, frequency of physical activities more than 60 minutes per week, fatigue recovery with the sleep, weight control effort, BMI, smoking, stress, subjective cognition of body type, subjective health, suicidal ideation and the agony counselor were drawn as the major factors having statistically significant influence on the subjective happiness received by Korean youths.Improvements/Applications: To enhance the happiness of the youth, the happiness enhancement program about breakfast management prevention of violence, physical activities more 60 minutes per week, sleep and fatigue recovery, weight control, smoking, stress management, suicidal ideation, counseling with the family as counselor, etc. is need to be activated.